HIF-1α is Critical for the Activation of Notch Signaling in Neurogenesis During Acute Epilepsy. (1st December 2018) - Li, Yushuang; Wu, Lei; Yu, Minhua; Yang, Fei; Wu, Bo; Lu, Shuting; Tu, Mengqi; Xu, Haibo
Highlights: The expression of HIF-1α was found to be upregulated in acute epilepsy. HIF-1α upregulation enhanced neurogenesis during epileptogenesis, which required the participation of Notch signaling. HIF-1α activated Notch signaling by physically interacting NICD in epilepsy. Abstract: Emerging evidence suggests that hypoxia-inducible factors (specifically, HIF-1α) and Notch signaling are involved in epileptogenesis and that cross-coupling exists between HIF-1α and Notch signaling in other diseases, including tumors and ischemia. However, the exact molecular mechanisms by which HIF-1α and Notch signaling affect the development of epilepsy, especially regarding neurogenesis, remain unclear. In the present study, we investigated the role of HIF-1α in neurogenesis and whether Notch signaling is involved in this process during epileptogenesis by assessing hippocampal apoptosis, neuronal injury, and the proliferation and differentiation of neural stem cells (NSCs) in four groups, including control, epilepsy, epilepsy+2-methoxyestradiol (2ME2) and epilepsy+GSI-IX (DAPT) groups. Our data demonstrated that HIF-1α mediated neurogenesis during acute epilepsy, which required the participation of Notch signaling. The immunoprecipitation data illustrated that HIF-1α activated Notch signaling by physically interacting with the Notch intracellular domain (NICD) in epilepsy. In conclusion, our results suggested that HIF-1α-Notch signaling enhanced neurogenesis in acute epilepsy and that neurogenesis during epileptogenesis was reduced once this pathway was blocked; thus, members of this pathway might be potential therapeutic targets for epilepsy.